2000
DOI: 10.1093/icb/40.4.664
|View full text |Cite
|
Sign up to set email alerts
|

Gravity-defying Behaviors: Identifying Models for Protoaves

Abstract: SYNOPSIS.Most current phylogenetic hypotheses based upon cladistic methodology assert that birds are the direct descendants of derived maniraptoran theropod dinosaurs, and that the origin of avian flight necessarily developed within a terrestrial context (i.e., from the ''ground up''). Most theoretical aerodynamic and energetic models or chronologically appropriate fossil data do not support these hypotheses for the evolution of powered flight. The more traditional model for the origin of flight derives birds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
(22 reference statements)
1
9
1
Order By: Relevance
“…Finally, since feather antecedents are likely to have appeared initially in small, gliding archosaurs from the middle Triassic Period (220 Myr; Fig. 1; Geist and Feduccia 2000;Jones et al 2000, the function of feathers or feather-like integumentary structures in dinosaurs is problematic.…”
Section: Metabolism and Thermoregulation In Amniotes Living And Extinctmentioning
confidence: 99%
“…Finally, since feather antecedents are likely to have appeared initially in small, gliding archosaurs from the middle Triassic Period (220 Myr; Fig. 1; Geist and Feduccia 2000;Jones et al 2000, the function of feathers or feather-like integumentary structures in dinosaurs is problematic.…”
Section: Metabolism and Thermoregulation In Amniotes Living And Extinctmentioning
confidence: 99%
“…(2000) and . Despite being based on a flawed methodology, the suggestion that Caudipteryx might be a flightless bird, and the implications this may have for feather origins, has been taken seriously and is included in a number of recent papers (e. g. Geist & Feduccia 2000, Martin & Czerkas 2000, Zhang & Zhou 2000. In this paper we re-evaluate the position of the centre of gravity in Caudipte~x, and show that its limb proportions argue convincingly against avian limb kinematics.…”
mentioning
confidence: 91%
“…As this is not the case it is really invalid to cite these characters as being indicative that Caudipteryx was a secondarily flightless bird. Ironically, according to the more traditional, functional and adaptational models of avian origins (Geist & Feduccia 2000, Tarsitano et al. 2000), an approach also favoured by Ruben & Jones (2000), the body proportions of Caudipteryx would effectively rule out its avian status!…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, with the advance of cladistic methods, all phylogenetic analyses have unanimously concluded that extant birds are a subgroup of the theropod dinosaurs, most often the sister taxon to the Dromaeosauridae (e. g. Gauthier 1986, Chiappe 1995, Dingus & Rowe 1998, Holtz 1994a, 1998, 2000, Makovicky & Sues 1998, Padian & Chiappe 1998, Sereno 1999). A minority of scientists, however, continue to advocate that birds are unrelated to theropod dinosaurs (e. g. Tarsitano & Hecht 1980, Feduccia 1985, 1996, Martin 1991, Feduccia & Wild 1993, Feduccia & Martin 1996, Geist & Feduccia 2000, Ruben & Jones 2000, Martin & Czerkas 2000; see also Gibbons (1998)). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation